Various Quantum- and Nano-Structures by III–V Droplet Epitaxy on GaAs Substrates - Wang Zh; Salamo GJ; Lee JH; Kim ES; Kim NY; Park SH (Nanoscale Research Letters, 2009)
Abstract We report on various self-assembled In(Ga)As nanostructures by droplet epitaxy on GaAs substrates using molecular beam epitaxy. Depending on the growth condition and index of surfaces, various nanostructures can be fabricated: quantum dots (QDs), ring-like and holed-triangular nanostructures. At near room temperatures, by limiting surface diffusion of adatoms, the size of In droplets suitable for quantum confinement can be fabricated and thus InAs QDs are demonstrated on GaAs (100) surface. On the other hand, at relatively higher substrate temperatures, by enhancing the surface migrations of In adatoms, super lower density of InGaAs ring-shaped nanostructures can be fabricated on GaAs (100). Under an identical growth condition, holed-triangular InGaAs nanostructures can be fabricated on GaAs type-A surfaces, while ring-shaped nanostructures are formed on GaAs (100). The formation mechanism of various nanostructures can be understood in terms of intermixing, surface diffusion, and surface reconstruction.